Knowledge and awareness regarding hepatitis B infection among medical and dental students: a comparative cross sectional study - Paul, Preetha; Arumugam, Balaji (International Journal of Research in Medical Sciences, 2017)
Background: Healthcare workers have a high risk of exposure to various infections like HIV, hepatitis B and C. Among these, the risk of exposure and infectivity is highest with hepatitis B. Sadly, among a majority of healthcare workers, awareness regarding this serious disease which is also preventable by vaccination, is lacking. This study was conducted with the objective of assessing the level of awareness and attitudes among medical and dental students regarding hepatitis B infection. Methods: This was a self-reported questionnaire-based study conducted among randomly selected medical and dental college students. The questionnaire included questions regarding hepatitis B infection, modes of transmission, vaccination schedule and attitudes towards hepatitis B patients in clinical practice. Results: A total of 246 students were interviewed of whom 144 (59%) and 102 (41%) were medical and dental students respectively. Overall, awareness levels were higher among medical students than dental students. We also found that female students were more knowledgeable than male students among both medical and dental student groups, with regard to awareness of hepatitis B infection as well as knowing the vaccination schedule, life-threatening complications and treatment and practice aspects. Approximately 60% of the dental students and less than 1% of the medical students were not vaccinated against hepatitis B. Conclusions: This study showed that overall awareness regarding hepatitis B is at a very basic level among the health care providers of the future and measures need to be taken to